ANALYSIS OF THE PLANNING OF STATE CIVIL APPARATUS RESOURCES AT THE WEST JAKARTA CITY ADMINISTRATION OF FIRE AND RESCUE AGENCY - Dian Wahyudin; Arie Iriawan (IJESS International Journal of Education and Social Science, 2022)
Apparatus Resource Planning in Fire department for several years has been stalled since 2014 due to moratorium policies of government toward acceptance of the state civil Apparatus. State of HR exicting at West Jakarta Fire Rescue Department still not good in term of quantity and quality. Starting from that point the author is encouraged to conduct research for finding solutions for lack of personnel in quality and quantity. Research objectives: first to analyze and evaluation of Apparatus Resource Planning at West Jakarta Fire Rescue Department. Second to know factors with inhibit in human resource planning at West Jakarta Fire Rescue Department. Third to find solution for resolving barriers in Human Resource Planning at West Jakarta Fire Rescue Department Methods used by the author in making thesis is a qualitative descriptive method. key person interviews, and literature review method of rules and regulation about fire fighter standards. In this research author reviewing problems that be found at West Jakarta Fire Rescue Department. In this research the author finds some research results among others: apparatus civil state resource palnning at West Jakarta Fire Rescue Department is not so good both in term of quality and quantity. Factors that affect the effectiveness of apparatus civil state resources planning at West Jakarta Fire Rescue Department among others is the release of civil servant moratorium since 2014. apparatus civil state resource planning at West Jakarta Fire Rescue Department is not so good both in terms of quality and quantity. Factors that affect the effectiveness of apparatus civil state resources planning at West Jakarta Fire Rescue Department among others is the release of civil servant moratorium since 2014. apparatus civil state resource planning at West Jakarta Fire Rescue Department is not so good both in terms of quality and quantity. Factors that affect the effectiveness of apparatus civil state resources planning at West Jakarta Fire Rescue Department among others is the release of civil servant moratorium since 2014.